Peran Mediasi Perceived Organization Support Pada Pengaruh Antara Religiusitas Terhadap Intrapreneurship Behavior Pada Dosen Perguruan Tinggi Swasta Di Yogyakarta - Maisaroh Maisaroh; Arief Darmawan (UNIVED Press, 2023)
Intrapreneurship is a form of behavior that appears in a company, with reference to entrepreneurship. Intrapreneurship behavior within the company is reflected in employees with high motivation in their work, who are full of creativity, and innovation, and who look for opportunities to complete work of the highest quality. This study tries to examine the role of the religiosity variable as an antecedent of intrapreneurship behavior of lecturers at private universities in Yogyakarta. By using data from 103 private university lecturer respondents in Yogyakarta, researchers tried to offer four hypotheses as a basis for data analysis tests. By using the PLS_SEM analysis tool, the results of the study prove that religiosity has a positive and significant effect on intrapreneurship and organizational support. Likewise, organizational support has a positive and significant effect on intrapreneurship. The role of organizational support as a mediating variable in the relationship between religiosity and intrapreneurship in this study showed insignificant results. This means that organizational support does not mediate the relationship between religiosity and intrapreneurship.